2009
DOI: 10.5539/elt.v2n3p44
|View full text |Cite
|
Sign up to set email alerts
|

Haunting Native Speakerism? Students’ Perceptions toward Native Speaking English Teachers

Abstract: This paper intends to explore how Taiwanese university students perceive their native-speaking English teachers (NESTs). Mutual expectations between the NESTs and students are also investigated. Collected data include questionnaires from 107 students and interviews with three NESTs and 19 students who have filled out the questionnaire. The result shows that students expect more encouragement and interaction with the NESTs, and more relaxed activities with fewer assignments and tests. A third of the students ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 25 publications
3
36
0
1
Order By: Relevance
“…Although numerous studies have been conducted into the matter, few have focused on students' perception of their English language teachers (e.g. Ling &Braine, 2007 andWu &Ke, 2009). In addition, few studies have been carried out in the Middle East (see for instance, Al-Issa, 2005;Alseweed and Daif-Allah, 2012;Daif-Allah, 2010;Zughoul, 2003).…”
Section: Context Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous studies have been conducted into the matter, few have focused on students' perception of their English language teachers (e.g. Ling &Braine, 2007 andWu &Ke, 2009). In addition, few studies have been carried out in the Middle East (see for instance, Al-Issa, 2005;Alseweed and Daif-Allah, 2012;Daif-Allah, 2010;Zughoul, 2003).…”
Section: Context Of the Problemmentioning
confidence: 99%
“…Differences between NESTs and NNESTs have been amply discussed, and arguments in favor or against each one have been tossed back and forth (see for example Alseweed and Daif-Allah, 2012;Braine, 2005;Ling and Braine, 2007;Liu, 2008;Madrid, 2004;Maum;Phillipson, 1992b;Todd and Pojanapunya, 2009;Wu & Ke, 2009).…”
Section: Context Of the Problemmentioning
confidence: 99%
“…Furthermore, this study showed the native English-speaking teachers' difficulties when dealing with the large-class management, insufficient teaching hours, and different level students in class. Finally, Wu and Ke (2009) mentioned that language learning and teaching are tied up with instructors and students; hence, they should be suggested to adjust their teaching approaches and learning strategies in different environment. Every individual has weakness, so only by this way can students and teachers benefit from learning and teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Research concerning the cultural differences in Taiwanese EFL senior high school speaking classes taught by native English-speaking teachers is comparatively rare and worth investigating (Wu & Ke, 2009). Ho (2004) argues convincingly that cultural understanding requires a reflection on one's own culture and on the cultures of others.…”
Section: Statement Of Problemsmentioning
confidence: 99%
“…As a result, they often tend to underperform in speaking 3 , which becomes a vital source of stress and anxiety. From Western perspective, the students seem to be passive, unresponsive, and unwilling to interact, as reported by Wu and Ke (2009).…”
Section: Research Contextmentioning
confidence: 98%